Benefits of specific strength training model with water resistance control gear for rowing and canoeing sports elite - Kvashuk, P. V.; Voronov, A. V.; Semaeva, G. N.; Maslova, I. N. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze benefits of a special strength training model with water resistance control gear for the rowing and canoeing sports elite, with muscle electrical activity tests of the key muscle groups. Methods and structure of the study. The muscle electrical activity tests in the special strength training model testing experiment were run using SportLab Computerized Test System (Russia-made) with an eight-channel telemetric electromy-ography unit, accelerometer, video cam, and a synch unit. Technical specifications of the test system and test procedures are described in detail in a prior study report.The study procedure was as follows. We sampled for the serial tests elite rowing and canoeing paddlers (n=5, three males and two females) qualified Candidate Masters and Masters of Sports. They were tested on a 90-110m distance by varied-intensity tests with application of water resistance control gear and/ or 6-14kg weights; with 5-8-min rest breaks. Every paddling style was played 2-3 times. We fixed the muscle electrical activity data by the skin electromyography (EMG) of the key right/left limb and trunk muscles versus the vessel speed and acceleration records. Every vessel was equipped with an accelerometer synchronized with the EMG test system and video cam - to read, among other things, the maximal vessel acceleration per stroke.We fixed the electrodes on the muscle convex centers, with no adjustments allowed in the experiment. The EMG data were inverted and smoothed by the moving average method with a 50ms averaging window. We profiled every single muscle's muscle electrical activity by standardized test cycles to produce averaged EMG amplitudes per stroke for every muscle. We tested on the whole five rowing styles at competitive speeds with water resistance control gear and 6/ 8/14kg weight application, when the paddlers were requested to work as hard as possible.Results and Conclusion. The study found that the water resistance control gear (water breaks) and weights may significantly change not only the electric signal amplitudes (i.e. the stroking power), but also the muscle electrical activity synchronization patterns. This trend was found to grow with weight or controlled water resistance. We also found that the water resistance stress and/or weights should never exceed 5-7% of the individual body mass for the special strength training efficiency. A special priority in trainings should be given to the rowing pace kept within the competitive range. High-speed paddling practices should be managed so as to keep within the competitive rowing standards to avoid potential damage for harmonized sport-specific muscle groups coordination patterns i.e. motor skills sets.